Beta through the prism of wavelets - Aasif Shah; Arif Tali; Qaiser Farooq (Financial Innovation, 2018)
In this paper, we empirically show how wavelet decomposition can provide an easy vehicle to study the systematic risk properties of return series to serve as protocol for different traders who view the market with different time resolutions. By using the separate catalogue of Large Cap, Mid Cap and Small Cap stocks comprising S&P BSE-500 index of Indian capital market, we report that the conventional beta coefficients estimated from CAPM are essentially an average of wavelet betas but the later provides a resolution more appropriate and hence need to be considered in a realistic risk assessment of securities. Additionally, the wavelet beta coefficients for Large Cap stocks are found more stable than Mid and Small capitalized stocks. This paper is the first attempt of its kind to link the underlying methodology across different capitalized stocks to identify the precise beta in a complex market behavior.
Keywords: C22; C49; G21; 650; CAPM; Beta; Wavelet